Longhorn beetles (Coleoptera: Cerambycidae) community composition around different boreal infrastructures - Sabina Noor; Emma Despland; Miguel Montoro Girona; Timothy Work (Journal of Environmental Management, 2026)

Translocating deadwood in ecological compensation benefits saproxylic beetles, but effects are dependent on substrate density - Olov Tranberg; Therese Löfroth; Anne-Maarit Hekkala; Mari Jönsson; Timothy Work; Heloise Gibb; Lukas Holmström; Jörgen Sjögren; Joakim Hjältén (Journal of Environmental Management, 2025)

Forest harvest causes rapid changes of maternal investment strategies in ground beetles - Lauren Egli; Timothy T. Work (Ecology, 2024)
Species recovery following anthropogenic disturbances will depend on adaptations in survivorship and fecundity. Life‐history theory predicts increased environmental stress will result in (1) shifts in resource allocation from fecundity to body growth/maintenance and (2) increased provisioning among offspring at the cost of reproductive output. For remnant populations that persist after forest harvesting, selection mediated through anthropogenic disturbances may affect resilience to additional stressors such as climate change. We tested how rapid changes in environmental conditions affected maternal investment strategies in two ground beetle species, Pterostichus pensylvanicus and Pterostichus coracinus , by comparing fecundity and survivorship in populations from recently clear‐cut and uncut habitats. Using parents drawn from clear‐cut or uncut stands, we reared progeny in both common garden and reciprocal transplant experiments. In P. pensylvanicus , we found that neither lineage nor rearing habitat affected the number of eggs laid per female or survivorship of offspring. However, eggs laid by females from clear‐cuts were more likely to hatch and offspring reached maturity more quickly, suggesting increased provisioning per offspring. In P. coracinus , females from clear‐cuts laid more eggs, and their eggs hatched more rapidly and had greater hatching success, suggesting increased investment in overall reproductive output and increased offspring provisioning. In the reciprocal transplant, we observed significant habitat by lineage interactions on survival in P. coracinus , with survivorship increasing when progeny were reared in novel habitats. In both species, increased maternal investment among offspring was not associated with a reduction in overall reproductive output, as anticipated. However, maternal investment among offspring declined with increasing female size, implying trade‐offs between increased metabolic demand and fecundity. Taken together, our work suggests that females from more stressful, clear‐cut habitats increased investment in fecundity, compared to females from uncut habitats, and may compensate for larval mortality. These changes were driven by smaller individuals, suggesting that increased environmental stress can influence the relationship between female size and maternal investment strategy. Additionally, reciprocal increases in offspring survivorship in habitats other than the parents suggest that adjacent areas between unharvested and clear‐cut habitat may be useful in maintaining biodiversity under future climate stressors.

Bryophyte community responses 20 years after forest management in boreal mixedwood forest - Marion Noualhaguet; Timothy T. Work; Maxence Soubeyrand; Nicole J. Fenton (Forest Ecology and Management, 2023)

Simulation and Analysis of the Effect of a Spruce Budworm Outbreak on Carbon Dynamics in Boreal Forests of Quebec - Zelin Liu; Changhui Peng; Louis De Grandpré; Jean-Noël Candau; Timothy Work; Chunbo Huang; Daniel Kneeshaw (Ecosystems, 2019)

Intercropping trees’ effect on soil oribatid diversity in agro-ecosystems - Enrique Doblas-Miranda; Alain Paquette; Timothy T. Work (Agroforestry Systems, 2014)

Interceptions of Nonindigenous Plant Pests at US Ports of Entry and Border Crossings Over a 17-year Period - Deborah G. McCullough; Timothy T. Work; Joseph F. Cavey; Andrew M. Liebhold; David Marshall (Biological Invasions, 2006)

Arrival rate of nonindigenous insect species into the United States through foreign trade - Timothy T. Work; Deborah G. McCullough; Joseph F. Cavey; Ronald Komsa (Biological Invasions, 2005)

Differences in ground beetles (Coleoptera: Carabidae) of original and reconstructed tallgrass prairies in northeastern Iowa, USA, and impact of 3-year spring burn cycles - Kirk J. Larsen; Timothy W. Work (Journal of Insect Conservation, 2003)